Transition from Tradition to Modernity: Health Challenges for Coastal Communities in Pematang Cengal Village - Dita, Dita; Diva, Diva; Ikrima, Ikrima; Khairunnisa, Khairunnisa; Nabila, Nabila; Wafida, Wafida; Wasiyem, Wasiyem (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Society is always experiencing change, and changes that occur in society are natural and unavoidable, even though changes in one society will be different from changes in other societies. Likewise with the modernization process. According to "The Random House Dictionary of the English Language", the word modern means or relates to the present and current; neither ancient nor remote, characteristic of the present and present; contemporary; neither ancient nor absolute. This means things related to the here and now; neither ancient nor archaic, typical of the present and present; contemporary; not old or outdated. The word modernity means the quality of being modern; something modern. This means quality with a modern feel; something modern. The word modernization means to make modern; to give a new or modern character or appearance, to be modern; adopting modern ways, views, etc. This means making it modern; giving new and modern characteristics or appearance, adopting oneself, a modern outlook and so on. 1 Based on the quote above, the meaning and meaning of the words modern, modernism, modernity and modernization are very clear